Improved apoptosis and mitochondrial dysfunction: the potential of carmofur-platinum nanoparticles - Erdemir-Cilasun, Gökçe; Özerkan, Dilşad; Kariper, İshak Afşin; Sert, Esra; Korkut, Işık Neslişah; Danışman-Kalındemirtaş, Ferdane (IOP Publishing, 2025)
Abstract Despite their impact on cancer therapy, limitations such as systemic toxicity and drug resistance are encountered with platinum-based drugs. This study explores the potential of combining PtIV-based NP with carmofur (Car) to address these issues. In this study, platinum nanoparticles (PtNPs) and Car-loaded PtNP (Car@PtNP) were synthesized and their cytotoxic and apoptotic effects on colorectal and breast cancer cells were evaluated. Following characterization of the synthesized NPs by dynamic light scattering, UV–VIS spectroscopy, FTIR, and STEM, it was found that the average size of PtNPs was 55.42 nm and the size increased to approximately 186.06 nm upon synthesis of Car@PtNP. MTT assays demonstrated that Car@PtNP exhibited higher levels of cellular toxicity than carmofur alone. While it significantly decreased cell viability in both colon and breast cancer cells, its toxicity to HUVEC cells was minimal. Treatment of MCF-7 and HCT116 cells with 50 µg ml−1 of free Car resulted in cell viabilities of 65.2% and 76.93%, respectively, whereas the viability of cells treated with Car@PtNP decreased to 49.60% and 55.47%. Flow cytometric analysis confirmed that apoptosis was increased in healthy HCT116 cells treated with Car@PtNP, with a marked increase in both early and late apoptotic cell populations. Furthermore, these results were confirmed by Hoescht and Rhodamin123 immunofluorescence staining, and significant mitochondrial dysfunction and apoptotic morphological changes were observed in treated cells. The findings underscore the promise of Car@PtNP as a novel chemotherapeutic approach, integrating the benefits of PtIV complexes and Car to enhance antitumor efficacy while mitigating the drawbacks of conventional platinum-based therapies.